1999
DOI: 10.1111/j.1365-2621.1999.tb15881.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Characteristics of Irradiated Aerobically Packaged Pork, Beef, and Turkey

Abstract: Color changes in irradiated meat were species-dependent. Irradiated pork and beef became less red as a result of irradiation and display time. The redness values of turkey increased after irradiation but decreased during display time. The yellowness of the irradiated samples, for all species, increased as a result of irradiation and display. Visual evaluation of irradiated pork and beef indicated an increase in brownness, whereas turkey increased in redness as dose increased. The surface color of irradiated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 13 publications
5
26
0
Order By: Relevance
“…Similar results have been reported in other studies in that no differences occurred between irradiated and nonirradiated samples with respect to yellowness (Luchsinger et al. 1997a,b; Nanke et al. 1998, 1999).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results have been reported in other studies in that no differences occurred between irradiated and nonirradiated samples with respect to yellowness (Luchsinger et al. 1997a,b; Nanke et al. 1998, 1999).…”
Section: Resultssupporting
confidence: 91%
“…Antioxidants increased chroma values back to those of control samples at day 0 (25.21). Similar results were reported by Nanke et al. (1999) in aerobically packaged and irradiated beef.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the same researchers22 determined that b * value increased from day 2 to 6 and decreased thereafter. Nanke et al 34 found that a * value decreased in turkey carcasses stored in aerobic conditions at 2 °C for 12 days. In the other study involving chicken carcass,35 it was reported that the L * value decreased (mean, 62.2), b * value increased (mean, 9.2), and a * value did not change (mean, 3.6) in breast fillets during storage at 4 °C for 7 days and that L *, a *, b *, C * and H * value were 61.6–58.4, 5.5–5.4, 7.2–7.0, 9.2–8.1, and 51.6–52.9 in leg muscles from days 0 to 7, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The color changes in irradiated meat differ significantly depending on various factors such as irradiation dose, animal species, muscle type, and packaging type (55,34,35,36). Increased redness is a problem in irradiated light meat such as poultry breast and pork loin, while brown or gray discoloration is the problem in irradiated red meat.…”
Section: Color Changes In Meat By Irradiationmentioning
confidence: 99%